2016
DOI: 10.1073/pnas.1606085113
|View full text |Cite
|
Sign up to set email alerts
|

Recommending teams promotes prosocial lending in online microfinance

Abstract: This paper reports the results of a large-scale field experiment designed to test the hypothesis that group membership can increase participation and prosocial lending for an online crowdlending community, Kiva. The experiment uses variations on a simple email manipulation to encourage Kiva members to join a lending team, testing which types of team recommendation emails are most likely to get members to join teams as well as the subsequent impact on lending. We find that emails do increase the likelihood that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…measured social identity as whether borrowers belong to a team, and they found that social identity has a positive influence on crowdfunding performance Ai et al (2016). also measured social identity as group membership and confirmed that social identity increases lending activities in a field experiment.…”
mentioning
confidence: 75%
“…measured social identity as whether borrowers belong to a team, and they found that social identity has a positive influence on crowdfunding performance Ai et al (2016). also measured social identity as group membership and confirmed that social identity increases lending activities in a field experiment.…”
mentioning
confidence: 75%
“…Burtch and Chan [11] examined a crowdfunding market for medical expenses and found that crowdfunding reduces personal medical bankruptcy rates. Few studies examined donation behaviors in online microlending markets and examined several factors influencing individuals' donation behavior, including the social, cultural similarity between donors and recipients [12,24], the language of loan requests [34,36], and joining a lending team [1].…”
Section: Literature Review 21 Gender Differences In Helpingmentioning
confidence: 99%
“…Studies showed that donors on microlending platforms tend to prefer recipients who are socially similar to themselves, and are sensitive to the language of loan requests [2,12]. Joining a lending team also promotes prosocial lending in online microlending [1]. While these studies advance our understanding of what affects prosocial lending decisions in online microfinance, we know little about whether the physical attractiveness of recipients influences prosocial donation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Like Cosley et al (2007), we also deploy a bot, ExpertIdeas Bot to post the experts' comments to the corresponding Wikipedia talk pages to standardize the format of the posts. Our approach demonstrates the potential of combining the predictive accuracy of machine learning with the causal inference of theory-guided field experiments in promoting prosocial behavior (Ai et al, 2016), representing a new wave of personalized intervention in economics.…”
Section: Literature Reviewmentioning
confidence: 99%